Analisis Peran Emosi Positif Pada Perilaku Impulse Buying Generasi Z Banyuwangi - Azid, Raka Malik; Supriyanto, Achmad Sani; Firmansyah, Fani (Jurnal Nusantara Aplikasi Manajemen Bisnis, 2024)
Research aim : This study aims to understand the effects of Islamic promotion, fashion involvement and hedonic shopping motivation on impulse buying by mediating positive emotions in Generation Z Banyuwangi. Design/Methode/Approach : This type of research is explanatory research and a quantitative approach. The sampling technique used the slovin technique, resulting in a total of 400 respondents. The data source utilizes survey data from online questionnaires with a Likert scale of 1-4. The analysis technique includes outer model testing and inner model testing with SmartPLS. Research Finding : The results of this study indicate that Islamic promotion, fashion involvement, hedonic shopping motivation and positive emotions have a positive and significant effect on impulse buying. Meanwhile, Islamic promotion and hedonic shopping motivation have a significant positive effect on impulse buying through positive emotions as mediation. However, the different results of positive emotions cannot mediate between fashion involvement and impulse buying. Theoretical contribution/Originality : Using Islamic promotional variables to implement appropriate marketing according to Islam and positive emotions as mediating variables are expected to have a significant effect both directly and indirectly. Practitionel/Policy implication : The implications of this research for e-commerce users as business actors, the use of Islamic promotions can encourage impulse buying among Generation Z in Banyuwangi Regency so as to increase sales of Muslim fashion products. For generation Z as consumers who shop with hedonic motives, fashion involvement, and positive emotions can trigger impulse buying, so that it has the potential for consumptive behavior. Research limitation : This research focuses on the impulse buying of Banyuwangi Z generation consumers who have shopped through e-commerce.